Kif15 Is Required in the Development of Auditory System Using Zebrafish as a Model - Zheng, Shimei; Tang, Dongmei; Wang, Xin; Liu, Chang; Zuo, Na; Yan, Renchun; Wu, Cheng; Ma, Jun; Wang, Chuanxi; Xu, Hongfei; He, Yingzi; Liu, Dong; et al. (Frontiers in Molecular Neuroscience, 2022)
Kif15, a kinesin family member, is powerful in the formation of bipolar spindles. There is emerging evidence indicating that Kif15 plays vital roles in influencing the growth of axons and interference with the progression of the tumor. However, the function of Kif15 in the auditory organs remains unknown. The Western blotting test was used to examine the effect of Kif15 downregulation by specific morpholino targeting Kif15 (Kif15-MO). The development of the inner ear and posterior lateral line (PLL) system in zebrafish was under continuous observation from spawns to 96 h postfertilization (hpf) to investigate the potential role of Kif15 in the auditory and vestibular system. We uncovered that Kif15 inhibition induced otic organ deformities in zebrafish, including malformed semicircular canals, abnormal number and location of otoliths, and reduced number of hair cells (HCs) both in utricle and saccule. Furthermore, a remarkable reduction in the number of PLL neuromasts was also explored in Kif15-MO morphants compared to the normal larvae. We also detected notably reduced activity in locomotion after Kif15 was knocked down. Additionally, we performed rescue experiments with co-injection of Kif15 mRNA and found that the Kif15 splicing MO-induced deformities in otic vesicle and PLL of zebrafish were successfully rescued, and the severely reduced locomotor activity caused by Kif15-MO was partially rescued compared to the control-MO (Con-MO) embryos. Our findings uncover that Kif15 is essential in the early development of auditory and vestibular organs using zebrafish as models.